Effect of the COVID-19 pandemic on infants’ development: analyzing the results of developmental assessments at ages 10–11 and 18–24 months - Otani, Takashi; Kato, Masaharu; Haraguchi, Hisami; Goma, Hideyo (Frontiers in Psychology, 2024)
The purpose of this study was to determine the effect of the COVID-19 pandemic on infant development. The study investigated the development of infants at 10-11 months of age between 2020 and 2023 by using the Kyoto Scale of Psychological Development-2020, an individualized developmental scale, and the Kinder Infant Developmental Scale (KIDS), a developmental questionnaire. We compared the results of the Kyoto Scale of Psychological Development-2020 (KSPD2020) with those of a pre-pandemic developmental research and compared the developmental age of KIDS with children's chronological age. Moreover, the same developmental research was conducted again on the same children at 18-24 months of age. Developmental age (DA) for receptive language and expressive language was lower in the KIDS compared to chronological age (CA) in the investigation at 10-11months. However, in the investigation at 18-24 months, there were no areas where KIDS' DA was lower than CA, and DA in the areas of manipulation, receptive language, social relationship with adults, discipline, and eating was higher than CA. On the other hand, using the KSPD2020, there were no differences when compared to pre-pandemic data in the investigation at 10-11months. Furthermore, the investigation at 18-24 months showed that developmental quotient (DQ) was lower in the Language-Social (L-S) areas than in the investigation at 10-11months. The lower DQ of L-S in this study was also evident in comparison to the 18-24 months pre-pandemic data. These results suggested that to investigate the medium-and long-term effects of the COVID-19 pandemic on children's development, it is necessary to use not only parent-filled questionnaires but also individualized developmental scales. In addition, the finding that results may differ depending on the method of developmental assessment is considered important not only for developmental researchers but also for professionals involved in supporting children's development.